Destructive arthritis with cutaneous polyarteritis nodosa requiring surgical intervention: a case report and review of the literature. (2nd July 2020) - Iwata, Takahiro; Ito, Hiromu; Furu, Moritoshi; Ishikawa, Masahiro; Azukizawa, Masayuki; Akiyama, Haruhiko; Matsuda, Shuichi
Abstract: Arthralgia is a well-known complication of cutaneous polyarteritis nodosa (CPN). However, few cases of destructive arthritis with CPN resulting in chronic pain and disability have been documented. Here we report a case of CPN associated with destructive arthritis of the right foot, accompanied by seronegative arthritis in the right ankle, for which orthopaedic surgery was necessary. X-ray and computed tomography revealed progressive joint destruction in the right talonavicular joint, and magnetic resonance imaging demonstrated severe synovitis of the right talocrural joint. When the talonavicular joint was opened, we observed marked synovitis and a defect in the cartilage that had expanded within the joint. Although mild cartilage degeneration was observed in the talocrural joint, arthroscopic observation revealed no massive defect on the articulated surface. Arthrodesis and arthroscopic synovectomy yielded a good midterm clinical outcome, indicating that surgical intervention was useful for the treatment for destructive arthritis with CPN. Rheumatologists and orthopaedic surgeons should be aware of potential complications such as destructive arthritis when treating patients with CPN.